Functional Cloning and Expression of the Schizophyllum commune Glucuronoyl Esterase Gene and Characterization of the Recombinant Enzyme. (4th July 2012) - Wong, Dominic W. S.; Chan, Victor J.; McCormack, Amanda A.; Hirsch, Ján; Biely, Peter
Abstract : The gene encoding Schizophyllum commune glucuronoyl esterase was identified in the scaffold 17 of the genome, containing two introns of 50 bp and 48 bp, with a transcript sequence of 1179 bp. The gene was synthesized and cloned into Pichia pastoris expression vector pGAPZα to achieve constitutive expression and secretion of the recombinant enzyme in soluble active form. The purified protein was 53 kD with glycosylation and had an acidic pI of 3.7. Activity analysis on several uronic acids and their derivatives suggests that the enzyme recognized only esters of 4- O -methyl-D-glucuronic acid derivatives, even with a 4-nitrophenyl aglycon but did not hydrolyze the ester of D-galacturonic acid. The kinetic values were K m 0.25 mM, V max 16.3 μM⋅min −1, and k cat 9.27 s −1 with 4-nitrophenyl 2- O -(methyl 4- O -methyl-α-D-glucopyranosyluronate)-β-D-xylopyranoside as the substrate.